2022
DOI: 10.1097/shk.0000000000001952
|View full text |Cite
|
Sign up to set email alerts
|

Early Differentiation Between Sepsis and Sterile Inflammation via Urinary Gene Signatures of Metabolic Dysregulation

Abstract: The aim of this study was to characterize early urinary gene expression differences between patients with sepsis and patients with sterile inflammation and summarize in terms of a reproducible sepsis probability score. Design: This was a prospective observational cohort study. Setting: The study was conducted in a quaternary care academic hospital. Patients: One hundred eighty-six sepsis patients and 78 systemic inflammatory response syndrome (SIRS) patients enrolled between January 2015 and February 2018. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Furthermore, given the significant variation in inciting cause of sepsis among patients, changes in host immune response, and those in response to therapeutic intervention, it is unsurprising that gene-expression profiles among patients change over time. Complicating matters further, the true onset of sepsis is imperceptible and can be substantially delayed among some patients (26,27). It is thus plausible that the lack of consensus to determining gene-expression signatures predictive of sepsis mortality in part stems from these critical issues related to timing and sampling differences between studies (28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the significant variation in inciting cause of sepsis among patients, changes in host immune response, and those in response to therapeutic intervention, it is unsurprising that gene-expression profiles among patients change over time. Complicating matters further, the true onset of sepsis is imperceptible and can be substantially delayed among some patients (26,27). It is thus plausible that the lack of consensus to determining gene-expression signatures predictive of sepsis mortality in part stems from these critical issues related to timing and sampling differences between studies (28).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, elevated biomarkers of anti-angiogenesis (i.e., Ang2, and sFlt-1) were observed. We also reported on a whole-genome analyses of RNA isolated from the urinary cells within 12 hours of sepsis onset 48,49 . A set of 239 genes was identified that shows excellent effectiveness in classifying septic patients from those with chronic systemic disease in both internal and independent external validation cohorts.…”
Section: Older Sepsis Patientsmentioning
confidence: 99%
“…We also reported on a whole-genome analyses of RNA isolated from the urinary cells within 12 hours of sepsis onset. 48,49 A set of 239 genes was identified that shows excellent effectiveness in classifying septic patients from those with chronic systemic disease in both internal and independent external validation cohorts. Functional analysis indexes revealed disrupted biological pathways in early sepsis and key molecular networks driving its pathogenesis.…”
Section: Acute Kidney Injurymentioning
confidence: 99%